جودة المعلومات ونظم دعم القرار ودورها على فاعلئة القرارات الأدارية دراسة ميدانية في وزارة التربية والتعليم في سلطنة عمان - Yousuf Hamed Marzouq Albadi
The aim of this study is to assess the potential relationships between the quality of the information used in making administrative decisions and the effectiveness of administrative decisions in the Ministry of Education in the Sultanate of Oman. It also aims to study the role of the intermediary of decision support systems in linking the effectiveness of administrative decisions on one hand and the quality of information on the other hand. The analytical descriptive method was used. Data were collected from 350 participants from the Omani Ministry of Education. Several advanced statistical methods were used, including exploratory factor analysis, confirmative factor analysis and structural modeling. The instrument was based on the previous studies and was subject to several tests to ensure that it was able to measure the relationships of this study. The instrument consisted of 52 paragraphs divided into three hypothetic components (information quality, decision support systems, and effectiveness of administrative decisions) and eight latent factors such as Formal Dimension, Post Content, Decision Support Systems, Quality Decision, Decision Making Time, Ease of Decision Execution and Decision Acceptance. The researcher tested the validity and reliability of instrument by expert arbitration, exploratory factor analysis and alpha coefficient. The results of the analysis showed that the paragraphs of instrument were loaded according to the researcher's expectations, with an alpha value ranging from 88 to 90 for each factor. This result indicates that the standard is of high quality and is suitable for use in scientific research. The result of the analysis revealed that the quality of the information is directly related to the effectiveness of the administrative decisions, and the decision support systems as an intermediary variable have also an indirect relationship with the effectiveness of administrative decisions. This finding shows that there is a direct and indirect relationship between the quality of information and the effectiveness of administrative decisions in the Ministry of Education in the Sultanate of Oman.